Natural Products for Pesticides Discovery: Structural Diversity Derivation and Biological Activities of Naphthoquinones Plumbagin and Juglone - Kaihua Wang; Beibei Wang; Henan Ma; Ziwen Wang; Yuxiu Liu; Qingmin Wang (Molecules, 2023)
Plant diseases and insect pests seriously affect the yield and quality of crops and are difficult to control. Natural products are an important source for the discovery of new pesticides. In this work, naphthoquinones plumbagin and juglone were selected as parent structures, and a series of their derivatives were designed, synthesized and evaluated for their fungicidal activities, antiviral activities and insecticidal activities. We found that the naphthoquinones have broad-spectrum anti-fungal activities against 14 types of fungus for the first time. Some of the naphthoquinones showed higher fungicidal activities than pyrimethanil. Compounds I, I-1e and II-1a emerged as new anti-fungal lead compounds with excellent fungicidal activities (EC50 values: 11.35–17.70 µg/mL) against Cercospora, arachidicola Hori. Some compounds also displayed good to excellent antiviral activities against the tobacco mosaic virus (TMV). Compounds I-1f and II-1f showed similar level of anti-TMV activities with ribavirin, and could be used as new antiviral candidates. These compound also exhibited good to excellent insecticidal activities. Compounds II-1d and III-1c displayed a similar level of insecticidal activities with matrine, hexaflumuron and rotenone against Plutella xylostella. In current study, plumbagin and juglone were discovered as parent structures, which lays a foundation for their application in plant protection.